Respuesta :

Answer:

Step-by-step explanation:

4x - 3y = 8 ------------------(I)

5x - 2y = -11 ------------------(II)

Multiply the equation (I) by (-5) and equation (II) by 4 and then add.

(I)*(-5)   -20x + 15y = -40

(II)*4       20x - 8y   = -44   {Now add, x will be eliminated}

                       7y   = -84

                         y = -84/7

                         y = -12

Plugin y = -12 in equation (I)

4x - 3*(-12) = 8

4x + 36 = 8

       4x = 8 - 36

        4x = -28

          x = -28/4

x = -7

ACCESS MORE